How tax policy and incentives affect foreign direct investment : a review - Morisset, Jacques (Policy research working paper, 2000)
Tax incentives neither make up for serious deficiencies in a country's investment environment nor generate the desired externalities. But when other factors, such as infrastructure, transport costs, and political and economic stability are more or less equal, the taxes in one location may have a significant effect on investors' choices. This effect varies, however, depending on the tax instrument used, the characteristics of the multinational company, and the relationship between the tax systems of the home and recipient countries